Plant community and ecosystem change on conservation reserve program lands in northeastern Colorado - Munson, Seth M., author (Colorado State University. Libraries, 2009)
The Conservation Reserve Program (CRP) is an important transitional land use that converts formerly cultivated land to perennial vegetation across the U.S. In the shortgrass steppe region of eastern Colorado, CRP currently includes nearly 1million hectares of land seeded with native and introduced perennial grasses. Establishment of perennial grasses encourages the recovery of plant community and ecosystem properties altered by tillage and crop production practices. The objective of my dissertation was to determine how time since CRP enrollment, seed mix, and environmental variability affect plant community composition, vegetation structure, net primary production, and soil carbon and nitrogen relative to undisturbed shortgrass steppe. As time since CRP enrollment increased, CRP fields transitioned from a species rich annual forb and grass community to a perennial grass dominated community with low species richness. Seed mix determined which perennial grasses increased in dominance, but slow and variable recovery allowed for a dynamic plant community composed of species with different life forms, photosynthetic pathways, and origins. Patterns of precipitation and interactions among species affected the relative differences in canopy cover between functional types. Vegetation structure was indirectly influenced by time since CRP enrollment and seed mix through plant community composition. There was an increase in plant basal cover and height, and decrease in plant density as perennial grasses replaced annual grasses and forbs. These structural attributes constrained aboveground net primary production (ANPP), but only when water was not limiting. CRP fields had the potential to support twice as much ANPP as undisturbed shortgrass steppe in years above mean annual precipitation. However, belowground biomass and belowground net primary production (BNPP) were significantly lower in CRP fields than undisturbed shortgrass steppe, which has implications for their long-term survival in a water limited region. Soil organic carbon was correlated to carbon input through BNPP from perennial grasses and increased at the plant scale as time since CRP enrollment increased. At the field scale, the carbon storage resulting from this increase was low in CRP fields compared to undisturbed shortgrass steppe. Nitrogen was closely linked to carbon in plants and soil and its availability was correlated to soil organic nitrogen, quantity an quality of belowground inputs, and precipitation.
Keywords: Conservation Reserve Program (U.S.); Grassland ecology -- Colorado -- Weld County